The role of the initial modality in the investigation of thyroid lesions - Tabassum, Farzana; Masud, Zafor M.; Hossain, Taslima; Karim, Saiyeda Sinthia (International Journal of Research in Medical Sciences, 2023)
Background: Partial or complete thyroidectomies are frequently encountered via the working towards pathologist and the opportunity of neoplastic disease is of principal problem in patients with thyroid nodules. Pathological comparison of these specimens ranged from non-neoplastic lesion to exceedingly aggressive malignancy. The aim of this study is to assess the role of the initial modality in the investigation of thyroid lesions. Methods: This is an observational study. The study used to be carried out in the admitted patient’s department of histopathology, National institute of ear, nose and throat, Dhaka. Bangladesh. In Bangladesh for the duration of the period from June 2021 to May 2022. Results: This study shows that according to 301 patients where, most of the patients in initial modality in the investigation of thyroid lesions 95 (31.56%) were 40 to 49 years and the minimum sex distribution of study 105 (34.88%) belongs to males. Non-neoplastic of goiter were 194 (64.45%), benign cyst was 43 (14.29%), DeQuervains (Subacute) thyroiditis 11 (3.65%), Lymphocytic thyroiditis were 8 (2.65%) and hashimoto thyroiditis were 3 (1.0%). And acfemalesg to neoplastic of papillary carcinoma were 30 (9.97%), Follicular neoplasm were 9 (2.99%) and Anaplastic carcinoma were 3 (1.0%). Conclusions: Thyroid lesions are more common in female. The majority of the thyroid nodules are either non-neoplastic or benign neoplasm. Thyroid lesions present a dependable analysis and is an incredible first line technique for investigating the nature of lesion.